Pengabdian Masyarakat Bertajuk Satu Langkah Kecil untuk Semangat Berbagi (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2024)
Community service activities carried out by lecturers and students of Sari Mutiara Indonesia University at the Elsadai Indonesia Orphanage with the theme "One Small Step for the Spirit of Sharing" have been carried out well on October 13, 2023. The target of this social service or social service activity is to focus on orphans and orphans. The form of this service activity is introductions, briefings or lectures, discussions and competitions or games. This social service activity aims to increase the sense of concern of lecturers and students in helping others in facing social problems such as limited education, economy, and social inequality. The community service that has been carried out is expected to inspire and motivate lecturers, especially the general public to share and care for each other.